2008
DOI: 10.1002/ceat.200800244
|View full text |Cite
|
Sign up to set email alerts
|

Recycle Effect on Double‐Pass Concentric Circular Mass Exchangers under Uniform Wall Fluxes

Abstract: A study on improvement in device performance of a double-pass concentric circular mass exchanger with uniform wall fluxes and external refluxes was conducted under counterflow operations. The linear superposition of an asymptotic solution and a homogeneous solution with the use of an orthogonal expansion technique for solving such a conjugated Graetz problem is formulated theoretically and the analytical predictions are applied to investigate a substantial masstransfer improvement. A mathematical expression fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The corresponding thermal penetration distance δ(τ) = δ 0 can be obtained by having ψ(0, τ) = 0 in Eq. (11).…”
Section: Before Ice Layer Meltingmentioning
confidence: 95%
See 1 more Smart Citation
“…The corresponding thermal penetration distance δ(τ) = δ 0 can be obtained by having ψ(0, τ) = 0 in Eq. (11).…”
Section: Before Ice Layer Meltingmentioning
confidence: 95%
“…Previous literatures [10,11] suggested that the advantageous effect of convective transfer coefficient increase suppresses the disadvantageous effect of transfer driving force decreasing in double-pass operations with recycle. In conjunction with our previous work [12], this article analyzes the recycle effect and the time variation of required air flow for given outlet chilled air temperature in a cool-thermal discharge system.…”
Section: Introductionmentioning
confidence: 98%